2010
DOI: 10.1111/j.1526-4610.2009.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

Triptan Use as a Function of Cardiovascular Risk. A Population‐Based Study

Abstract: Triptan use is lower in those with vs without CV risk, suggesting that doctors and/or patients fear using triptans in individuals at risk to CVD. Furthermore, triptan use in those with established CVD increases with headache-related disability, suggesting that patients and providers balance risks and benefits. Additional and analytical data are needed on the safety of triptans in the setting of CVD risk. This study has not assessed adequacy of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…Similar results were obtained for subjects with migraine with aura and migraine without aura overall (3, 26). In the same population, the prevalence of diabetes did not differ between subjects with episodic and chronic migraine (27).…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were obtained for subjects with migraine with aura and migraine without aura overall (3, 26). In the same population, the prevalence of diabetes did not differ between subjects with episodic and chronic migraine (27).…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with published research in which the risk of CV risk factors among adults with migraine is higher than those without migraine [14, 15]. Bigal et al reported that the prevalence rate of CV risk factors such as diabetes (12.6%), hypertension (33.1%), hyperlipidemia (32.7%), and smoking (15.8%) was significantly higher among adults with migraine as compared to adults without migraine [10]. …”
Section: Discussionsupporting
confidence: 90%
“…The AMPP study reported that triptans use among those with no CV risk factors was 18.3% [10]. The difference in rates of triptans use may be due to differences in study population and the definition of CV risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraine is intimately linked to cardiovascular disease (CVD) . Migraine, particularly migraine with aura, is a risk factor for CVD events, including myocardial infarction and stroke, and is associated with increased cardiovascular (CV) mortality .…”
Section: Introductionmentioning
confidence: 99%